Analysis of risk factors for pneumothorax after particle implantation in the treatment of advanced lung cancer after surgery and establishment of a nomogram prediction model - Ding, Tingting; Hao, Shanhu; Wang, Zhiguo; Zhang, Wenwen; Zhang, Guoxu (Frontiers in Medicine, 2024)
Objective: To analyze the risk factors for pneumothorax after particle implantation in the treatment of advanced lung cancer and to construct and validate a nomogram prediction model. Methods: A retrospective analysis was conducted on 148 patients who underwent 125 I particle implantation for advanced lung cancer at the *** from December 2022 to December 2023. Potential risk factors were identified using univariate logistic regression analysis, followed by a multivariate logistic regression analysis to evaluate the predictive factors for pneumothorax. Interaction effects between variables were studied and incorporated into the model construction. ROC curves and nomograms were generated for visualization. Calibration analysis was performed, and the corresponding net benefit was calculated to adjust the predictive model. Results: Among the 148 patients, 58 (39.19%) experienced pneumothorax, with a mean age of 62.5 (55.25, 70) years. Multivariate analysis showed that the angle between the puncture needle and the pleura <50 °(P=0.002, OR: 3.908, CI:1.621-9.422), preoperative CT suggesting emphysema (P=0.002, OR: 3.798, CI:1.600-9.016), atelectasis (P=0.009, OR: 3.156, CI: 1.331-7.481), and lesion located in the left lung fissure (P=0.008, OR: 4.675, CI: 14.683) were independent risk factors for pneumothorax after particle implantation in the treatment of advanced lung cancer.Preoperative CT suggesting lesions in the left lung fissure or suggesting emphysema had a significant impact in the nomogram, with probabilities of pneumothorax occurrence at 40% and 38%, respectively. The predictive AUC for the above four risk factors for pneumothorax after particle implantation in the treatment of lung adenocarcinoma was 0.837 (95% CI: 0.767-0.908). When the Youden index was 0.59, the sensitivity was 85.56%, specificity was 74.13%, accuracy was 81.01%, positive predictive value was 83.69%, and negative predictive value was 76.78%.The angle between the puncture needle and the pleura <50 °, preoperative CT suggesting emphysema, atelectasis, and lesion located in the left lung fissure are independent risk factors for pneumothorax after particle implantation in the treatment of advanced lung cancer. Preoperative planning of the puncture path should avoid lung bullae, interlobar fissures, areas of severe emphysema, and atelectasis.